2019
DOI: 10.1017/mor.2018.38
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of European Intellectual Property Institutions on Chinese Outward Foreign Direct Investment

Abstract: This study examines the role of the strength of the Intellectual Property (IP) institutions of 23 European countries in attracting Chinese Outward Foreign Direct Investment (OFDI) during the time period 2003–2015. Following a dynamic panel data analysis methodology, we find that the strength of IP institutions has a positive effect in attracting higher levels of OFDI from China. This is an important finding for the OFDI literature from emerging markets, since previous studies have researched this relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 89 publications
(181 reference statements)
0
10
1
Order By: Relevance
“…In the process of OFDI's reverse green technological innovation spillover effect, the protection of intellectual property rights is neither as small nor as large as it could be. Instead, there is an optimal interval-as suggested in Park's "optimal IPP interval hypothesis" [29].…”
Section: Empirical Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In the process of OFDI's reverse green technological innovation spillover effect, the protection of intellectual property rights is neither as small nor as large as it could be. Instead, there is an optimal interval-as suggested in Park's "optimal IPP interval hypothesis" [29].…”
Section: Empirical Results and Analysismentioning
confidence: 99%
“…ey found that market size and political environment are also essential factors of OFDI. After conducting a field inspection of the IPP systems in 23 countries, Papageorgiadis et al [29] analyzed the differences in the level of China's foreign direct investment. ey found that Chinese enterprises are more likely to invest in countries with weak IPP systems.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…This can act as a deterrent of IPR infringing activities, discouraging the opportunistic behaviour of domestic firms that might consider to infringe the IPR of an MNE but eventually refrain from doing so due to the high risk of being prosecuted and penalized. In contrast, in countries where public IPR enforcement is weak, even if an MNE pursues a litigation case against infringers, the firm will find it difficult and problematic to effectively enforce its rights in practice (Papageorgiadis et al 2019bYang et al 2008). This is because the judiciary may delay the delivery of a judgement on an IPR case and, if the defendant is found guilty, award penalties that are not punitive and/or of limited impact on the operations of the infringer (Brander et al 2017).…”
Section: Public Ipr Enforcement and Inward Fdi Horizontal Productivity Spilloversmentioning
confidence: 99%
“…Intellectual capital (CI) integrates the intangible assets of companies, helping them compare their performance and the achievement of sustainable success (Dinh, Kang, Morris, & Schultze, 2018). This research considers three aspects of intellectual capital: human, organizational and technological, each with its own characteristics (Papageorgiadis, Xu, & Alexiou, 2019). For example, human capital refers to company personnel, who apply the knowledge, skills and abilities to develop work activities (Antoni, Maug, & Obernberger, 2019).…”
Section: Introductionmentioning
confidence: 99%